SIMULTANEOUS QUANTIFICATION OF PENTAZOCINE AND NALOXONE BY STABILITY INDICATING REVERSE-PHASE-HIGH-PERFORMANCE LIQUID CHROMATOGRAPHIC METHOD: PENTAZOCINE AND NALOXONE HPLC ANALYSIS - RAMA KUMAR KANDULA; RAJA SUNDARARAJAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to develope a stability indicating high-performance liquid chromatographic (HPLC) method for simultaneous assay of pentazocine and naloxone in bulk and tablets. Methods: Pentazocine and naloxone were analyzed on Dionex C18 column using 0.1M K2HPO4 buffer (pH 4.0) and methanol (60:40, v/v) as the mobile phase. The concentration of pentazocine and naloxone was quantified by photodiode array detector set at 248 nm. The method was validated in compliance with ICH rules. Pentazocine and naloxone tablet formulation was subjected to forced degradation such as acid, neutral and alkali hydrolysis, oxidation, photo, and thermal degradation. Results: The method was linear, with R2=0.9999 in the concentration range 100–300 μg/ml for pentazocine and R2=0.9995 in the concentration range 1–3 μg/ml for naloxone. The level of detection and quantification was 0.097 μg/ml and 0.322 μg/ml for pentazocine and 0.0073 μg/ml and 0.0243 μg/ml for naloxone, respectively. The degraded products are resolved well from pentazocine and naloxone with significantly different retention time values. From validation results, it was proved that the method is selective, precise, robust, and accurate for the estimation of pentazocine and naloxone simultaneously. Conclusion: The developed stability-indicating HPLC method can be applied for quantitative determination of pentazocine and naloxone in tablets.